Cartographies of the diference in the curricular research and in the teaching of Natural Sciences and Mathematics (Research, Society and Development, 2020)
The philosophy of the difference has led to discussions that have contributed to the field of teaching and curriculum theorization. In this way, we identified the need to carry out this research in order to have an overview of what has been produced, discussed and tensioned about the perspective of this thought with regard to the curriculum in science education. The methodological path was established from Cartography, analyzing the works already produced. We chose the Google Scholar Digital Bank (Google Scholar), having as descriptors: Philosophy of Difference, Curriculum; Science teaching; Deleuze and Guattari, between the years 2009 to 2020. There were (74/14) works. We identified with concern the small number of works that address this topic.